2012
DOI: 10.7740/kjcs.2012.57.1.089
|View full text |Cite
|
Sign up to set email alerts
|

Soil Greenhouse Gas Emissions from Three Decades Long-term Experimental Field of Corn-Soybean Rotation and Tillage Treatments

Abstract: Reduction of greenhouse gas (GHG) emissions from upland crop field as well as paddy field is being required, but little information on GHG emissions according to cultivation practices in upland field is available. Soil GHG emissions during the growing season were investigated in the field of three decades rotation and tillage treatments which were consisted of plow, chiesl tillage and no tillage in west central Indiana, USA in 2006. Seasonal cumulative CO 2 emissions were not different among treatments. CH 4 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…But the focus of these studies has been about crop growth and productivity; the environmental aspects of different management practices have not been well explored as yet. Studies related to source control for the development of BMPs have been reported by a few researchers (Choi et al , , ; Shin et al , , ; Won et al , ; Seo et al , ). These studies mostly focused on the effect of rice straw surface cover, PAM, and gypsum (and their combination) on soil erosion, runoff and NPS pollution from sloping fields.…”
Section: Introductionmentioning
confidence: 99%
“…But the focus of these studies has been about crop growth and productivity; the environmental aspects of different management practices have not been well explored as yet. Studies related to source control for the development of BMPs have been reported by a few researchers (Choi et al , , ; Shin et al , , ; Won et al , ; Seo et al , ). These studies mostly focused on the effect of rice straw surface cover, PAM, and gypsum (and their combination) on soil erosion, runoff and NPS pollution from sloping fields.…”
Section: Introductionmentioning
confidence: 99%